Low-cost chitosan-calcite adsorbent development for potential phosphate removal and recovery from wastewater effluent. (15th April 2020) - Pap, Sabolc; Kirk, Caroline; Bremner, Barbara; Turk Sekulic, Maja; Shearer, Lisa; Gibb, Stuart W.; Taggart, Mark A.
Abstract: Phosphorous (P) recovery from wastewater will become increasingly vital in the future as terrestrial rock phosphate deposits are expended. Effective management of P as a critical resource will require new techniques to recover P from wastewater, ideally in a form that can be used in agriculture as fertiliser. In this study, batch and fixed-bed column conditions were tested using a novel KOH deacetylated calcite-chitosan based adsorbent (CCM) for P removal from aqueous solutions and wastewater effluents. The unique characteristics of this adsorbent as a phosphate adsorbent were the result of rich surface functionality (amine and sulphur functional groups of the chitosan and proteins) and the CaCO3 content (providing donor ligands; and additionally beneficial if the material were used as fertiliser, buffering soil acidification caused by nitrogen application). The maximum P adsorption capacity was determined to be 21.36 mgP/g (at 22 °C) and the endodermic process reached equilibrium after 120 min. The experimental data was best described using a Langmuir isotherm and a pseudo-second order kinetic model. The diffusion kinetic analysis highlighted the importance of both film and intraparticle mass-transport. Material characterisation suggested that the adsorption process involved interactions between P and functional groups (mostly –NH3 + ) due to electrostatic interaction on the chitosan chain or involved ligand exchange with CO3 2− . Analysis of materials using X-Ray Powder Diffraction (XRPD) and Thermogravimetric Analysis (TGA) indicated a microprecipitation-type mechanism may occur through the formation of hydroxylapatite (Ca5 (PO4 )3 (OH)). Desorption studies demonstrated that the P-laden CCM (derived from crab carapace) had the potential to be reused in soil amendment as a slow-release P fertiliser. The effects of different operating parameters were explored in a fixed-bed column, and the experimental data fitted well to the Clark model ( R 2  = 0.99). The CCM also showed excellent P adsorption potential from secondary and final wastewater effluent in dynamic conditions, even at low P concentrations. Finally, a scale-up approach with cost analysis was used to evaluate the price and parameters needed for a potential large-scale P recovery system using this adsorbent. Graphical abstract: Image 1 Highlights: KOH deacetylation was used to synthesise a calcite-chitosan rich adsorbent. The adsorbent showed a high adsorption capacity (21.56 mg P/g) for P. Inner- and outer-sphere complexation with Ca–P microprecipitation were the major adsorption mechanisms. A desorption study indicated the adsorbent's potential as a fertiliser type product. Scale-up with pilot plant design were implemented.